PENERAPAN TERAPI BICARA A.I.U.E.O UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI VERBAL PADA PASIEN STROKE NON HEMORAGIK DI RUANG REHABILITAS MEDIK RSUD CIBABAT - Yulianti, Ami; Octaviani, Oky; Malisa, Novi (Yayasan Putra Sukamanah Sejahtera, 2025)
Stroke is the second leading cause of death after heart disease and the third leading cause of disability worldwide (American Heart Association, 2020). Non-hemorrhagic stroke refers to a decline in brain function due to disrupted blood supply to parts of the brain, resulting in vessel blockage or narrowing. This study aimed to evaluate the effectiveness of A.I.U.E.O speech therapy in enhancing verbal communication in non-hemorrhagic stroke patients in the medical rehabilitation unit at Cibabat Regional General Hospital. A.I.U.E.O speech therapy is an intervention that supports improved verbal communication in patients with speech disorders. This case study used a nursing process approach involving two patients with impaired verbal communication. The intervention was administered for 3 consecutive days, with each session lasting 15 minutes. Results showed improved verbal communication abilities by the third day following at least three therapy sessions. Patient 1 could articulate words clearly, construct longer sentences, showed more responsive facial expressions, improved conversation comprehension, and experienced reduced slurred speech. Patient 2 could articulate several words, showed responsive facial expressions, moderately improved conversation comprehension, and had moderate slurring. Contributing factors included diet in patient 1 and excessive stress in patient 2, which slowed recovery. In conclusion, A.I.U.E.O speech therapy is effective in enhancing verbal communication abilities in non-hemorrhagic stroke patients and is recommended as part of nursing care to support stroke rehabilitation.